Crazy sexy diet : eat your veggies, ignite your spark, and live like you mean it! - Carr, Kris (Skirt, 2011)
The author of Crazy Sexy Cancer Tips takes on the subject of what and how we eat, drink, and think. Along with help from experts, the author lays out the fundamentals of a low-glycemic, vegetarian program that emphasizes balancing the pH of the body with whole and raw foods, organic green drinks, and smoothies. She shares the steps of her own twenty one day cleanse, and simple but delectable sample recipes. In addition to debunking common diet myths and sharing vital tips on detoxifying our bodies and psyches, she provides helpful hints on natural personal care, how to stretch a dollar, navigate the grocery store, eating well on the run, and working through the inevitable pangs and cravings for your old, not so healthy life.